2021
DOI: 10.33785/ijds.2021.v74i05.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic and non genetic factors on production performance of primiparous Kankrej cattle

Abstract: The effects of genetic and non genetic factors on performance traits (Daily Milk Yield, 305 Days Milk Yield, Total Milk Yield and Lactation Length) of primiparous Kankrej cows was studied. The least square means of daily milk yield, 305 days milk yield, total milk yield and lactation length were calculated and found 6.71±0.14, 1893.42±60.00, 1983.29±72.47 kg and 290.78±7.33 days, respectively. The season and period of calving did not affect these traits, while effects of sire was significant (*P<0.05) on 305… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…However, Kumar et al (2022) observed non-significant effects on LMY in Sahiwal cattle. Non-significant effects on LMY, ADMY and LL for Kankrej cattle were observed by Thakkar et al (2021). The presence of significant seasonal effect on LMY, ADMY and LL might be an indication of the difference in management practices and availability of feeds and fodder during different seasons.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Kumar et al (2022) observed non-significant effects on LMY in Sahiwal cattle. Non-significant effects on LMY, ADMY and LL for Kankrej cattle were observed by Thakkar et al (2021). The presence of significant seasonal effect on LMY, ADMY and LL might be an indication of the difference in management practices and availability of feeds and fodder during different seasons.…”
Section: Resultsmentioning
confidence: 92%
“…Note: Least square means and standard errors with different superscripts differ significantly at P<0.05 Thakkar et al (2021). in Kankrej cattle observed higher LMY, ADMY and LL.Kumar et al (2022) in case of Sahiwal cows reported a higher LMY Shahid et al (2022).…”
mentioning
confidence: 94%
“…Thakkar et al. (2021) reported that season and period of calving did not reveal significant association with production traits. Mundhe et al.…”
Section: Discussionmentioning
confidence: 98%
“…also reported that season of calving had no significant on FLTMY and first LL Togla et al (2021). reported that 305-days MY was found to be significantly (p < .05) affected by parity while Lifetime milk production was significantly (p < .05) affected by parity and season of calving Thakkar et al (2021). reported that season and period of calving did not reveal significant association with production traits Mundhe et al (2015).…”
mentioning
confidence: 93%
“…Among genetic and non-genetic factors that influence the cows' dairy productivity, the following factors have been proved to have a strong influence, namely: the sire group (Choudhary et al, 2019;Thakkar et al, 2021), lactation number, i.e., the cow's age (Gorgulu, 2011;Bolacali & Öztürk, 2018;Marumo et al, 2022), cow age at first insemination or first pregnancy (Gorgulu, 2011;Eastham et al, 2018;Adamczyk et al, 2018), a season of the year (ElBoshra et al, 2016), the inter-calving interval (Němečková et al, 2015;Bujko et al, 2018), dry period length (Gorgulu, 2011), and others.…”
Section: Signmentioning
confidence: 99%